2011
DOI: 10.1139/z11-072
|View full text |Cite
|
Sign up to set email alerts
|

Feeding performance in the Western Ribbon Snake (Thamnophis proximus): ontogeny and the effects of prey type and size

Abstract: It has been suggested that juveniles have exaggerated morphologies or improved performance to compensate for the disadvantages of being small. As gape-limited predators, juvenile snakes are at a particular disadvantage in terms of prey availability, capture, and ingestion. Prey preference often changes with snake size yet previous studies generally compare only one prey type or relative prey size among age classes. Using Western Ribbon Snakes ( Thamnophis proximus (Say in James, 1823)), I investigated the onto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…This pattern does not seem to hold true for snakes when performance is a measure of the effort required to consume a prey item (Vincent et al, 2007;Hampton, 2011a) (this study). While studies have shown that relative prey size affects the time and functional effort required for ingestion (Pough and Groves, 1983;Hampton, 2011a), ingestion performance does not explain the allometry of trophic morphology when corrected for prey size. Large snakes typically consume a disproportionately high number of small prey, which is thought to be a consequence of prey availability (Voris and Moffett, 1981).…”
Section: Ingestion Performancementioning
confidence: 67%
See 4 more Smart Citations
“…This pattern does not seem to hold true for snakes when performance is a measure of the effort required to consume a prey item (Vincent et al, 2007;Hampton, 2011a) (this study). While studies have shown that relative prey size affects the time and functional effort required for ingestion (Pough and Groves, 1983;Hampton, 2011a), ingestion performance does not explain the allometry of trophic morphology when corrected for prey size. Large snakes typically consume a disproportionately high number of small prey, which is thought to be a consequence of prey availability (Voris and Moffett, 1981).…”
Section: Ingestion Performancementioning
confidence: 67%
“…The heads of snakes play many functional roles, and various ecological pressures may constrain which bones are modified and to what limit. While the number of jaw protractions required to ingest prey varies among snake species (Pough and Groves, 1983), head size has not been shown to influence ingestion time or jaw protractions within a species (Vincent et al, 2007;Hampton, 2011a). This suggests that other factors are influencing head size and shape.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations